Pre-ozonation of source water: Assessment of efficacy against Giardia duodenalis cysts and effects on natural organic matter. (January 2019) - Nakada, Liane Yuri Kondo; Franco, Regina Maura Bueno; Fiuza, Vagner Ricardo da Silva; Santos, Luciana Urbano dos; Branco, Nilson; Guimarães, José Roberto
Abstract: The protozoan Giardia duodenalis is one of the parasites of primary concern in drinking water treatment plants, due to its resistance to chlorination. Another matter of concern regarding chlorination of drinking water is the formation of disinfection by-products in the presence of precursors such as natural organic matter (NOM). In this study, the effects of ozonation (5 mg L −1 ) on G. duodenalis cysts in raw surface water from a drinking water treatment plant were evaluated, and the presence and alteration of NOM were assessed, as an indicative of the potential to prevent total organic halogen (TOX) formation during post-chlorination. Following ozone treatment, the presence of damaged cysts was observed by direct immunofluorescence assay (IFA) and confirmed by the molecular approach propidium monoazide-polymerase chain reaction (PMA-PCR). Using an animal model, analysis of the intestinal tissues revealed that 80% of the animals inoculated with ozonated water were positive for trophozoites. This study shows that analysis of intestinal fragments is imperative to accurately assess animal infection following inoculation of treated cysts. More importantly, considering the low infective dose of Giardia cysts in susceptible hosts, an ozone dosage usually applied in drinking water treatment plants did not completely inactivate G. duodenalis cysts in surface water. Nonetheless, the results suggest that competitive reactions with NOM have occurred, and the applied ozone dosage has proven useful to remove NOM reactivity, and thus prevent halogenated DBP formation during post-chlorination. Highlights: Three methods were used to evaluate ozonation against G. duodenalis in river water. Results obtained by IFA and PMA-PCR are consistent with findings from in vivo assay. Ozonation did not yield complete inactivation of G. duodenalis cysts. Results suggest that competitive reactions with NOM have occurred. Ozone has proven useful to remove up to 76.8% of NOM reactivity.